A Stegodon Mandible from Cipanaruban, Subang, West Java; Description and Its Position in the Java Vertebrate Biostratigraphy - Unggul Prasetyo Wibowo; Erik setiyabudi; Iwan Kurniawan (Pusat Survei Geologi, 2018)
Abstract - This paper describes a fossil of a right mandibular ramus with nearly complete molar M2 of Stegodon from a cliff of a hill of Cipanaruban River, near Pasir Cabe, about 6 km to the East of Subang City, West Java, Indonesia. The specimen is a surface collected, however the attached matrix on mandible indicated that this specimen is mostly derived from the sandstone unit of the Citalang Formation. The age of this fossil is estimated to be around Late Pliocene to Early Pleistocene based on the mammalian biostratigraphy of Java.Keyword : Stegodon, mandible, Late Pliocene - Early Pleistocene, fossil, Subang.